2003
DOI: 10.1073/pnas.2332656100
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of unidirectional Pito ATP flux in human visual cortex at 7 T by usingin vivo31P magnetic resonance spectroscopy

Abstract: Taking advantage of the high NMR detection sensitivity and the large chemical shift dispersion offered by ultra-high field strength of 7 T, the effect of magnetization transfer on inorganic phosphate (Pi) resonance during saturation of ␥-ATP resonance, mediated by the ATP synthesis reaction, was observed noninvasively in the human primary visual cortex by using in vivo 31 P magnetic resonance spectroscopy. The unidirectional flux from Pi to ATP was measured by using progressive saturation transfer experiments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
154
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(175 citation statements)
references
References 43 publications
(75 reference statements)
18
154
3
Order By: Relevance
“…Consequently, pH values measured in our study are likely to represent intracellular pH, under physiological as well as under pathological conditions. Recent in vivo MRS data suggest that a large majority of brain Pi is located in neurons as opposed to glial cells, based on the fact that Pi is in a compartment where oxidative metabolism strongly dominates glycolytic metabolism (Chaumeil et al, 2009;Lei et al, 2003). Altogether, these observations allow us to interpret our results as an increase in neuronal pH in HD.…”
Section: Arguments For Intracellular Neuronal Ph Increasesupporting
confidence: 60%
“…Consequently, pH values measured in our study are likely to represent intracellular pH, under physiological as well as under pathological conditions. Recent in vivo MRS data suggest that a large majority of brain Pi is located in neurons as opposed to glial cells, based on the fact that Pi is in a compartment where oxidative metabolism strongly dominates glycolytic metabolism (Chaumeil et al, 2009;Lei et al, 2003). Altogether, these observations allow us to interpret our results as an increase in neuronal pH in HD.…”
Section: Arguments For Intracellular Neuronal Ph Increasesupporting
confidence: 60%
“…In contrast, we have recently demonstrated that the unidirectional Pi 3 ATP rate measured by the in vivo 31 P MT approach in the resting human brain was consistent with the oxidative ATP synthesis rate (9). This finding has led us to hypothesize that the in vivo 31 P MT approach could provide a unique and completely noninvasive tool for quantita-tively determining the oxidative ATP synthesis rate in the brain, which is vital for studying the cerebral bioenergetics and brain function (9). In the present study, we test this hypothesis and attempt to establish a noninvasive 31 P MRS approach for directly and quantitatively measuring the rate of oxidative phosphorylation and its change in the brain.…”
mentioning
confidence: 66%
“…The brain ATP metabolism is mainly controlled by ATPase and creatine kinase (CK) reactions that are coupled together and constitute a complex chemical exchange system involving ATP, phosphocreatine (PCr), and intracellular inorganic phosphate (Pi) (i.e., a PCr^ATP^Pi chemical exchange system) (7)(8)(9)(10). One vital function of this ATP metabolic network is to maintain a stable cellular ATP concentration by adjusting the reaction rates to ensure a continuous energy supply for sustaining electrophysiological activity and maintaining normal function in the brain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…of arterial blood 9,000 nmoL/mL Glucose conc. of arterial blood 5,000-6,000 nmoL/mL 53 Oxygen extraction fraction 30%-55% 3,5,6,27,75,93 Glucose extraction fraction 8%-15% ATP concentration of brain tissue 1,000-3,000 nmoL/mL 124,137,138 Total ADP concentration of brain tissue 300 nmoL/mL 124,138 Free ADP concentration of brain tissue 30-35 nmoL/mL [121][122][123] PCr concentration of brain tissue 4,000-5,000 nmoL/mL 123,124,138 Diffusion constant for O2 in brain 78 Assuming mitochondrial oxygen tension close to zero (meaning so low that any further reduction would limit oxidative metabolism), the driving force for oxygen delivery, the gradient between the capillary and mitochondria, can only be increased by an increase in capillary oxygen tension, which in turn requires a decrease of the oxygen extraction fraction. Later, the observation of constant CMRO 2 during pharmacological reductions of CBF led to a modification of the model by incorporating potential changes of cytochrome c oxidase affinity to oxygen during increases in neuronal activity.…”
Section: Differences Of Oxygen and Glucose Supplymentioning
confidence: 99%